2015
DOI: 10.1556/0806.43.2015.001
|View full text |Cite
|
Sign up to set email alerts
|

Allelic diversity of HMW and LMW glutenins in Indian wheats and their relationship with sedimentation volume and mixograph parameters

Abstract: Two hundred and forty diverse set of wheat cultivars released in India during the last several decades were evaluated for HMW and LMW glutenin alleles, for assessing their diversity and effect on sedimentation volume and mixograph parameters. Both SDS-PAGE and PCR based markers were employed in identifying alleles encoded at Glu-1 and Glu-3 loci. Extensive allelic variation was observed at both the Glu-1 and Glu-3 loci. There was prevalence of Glu-A1b, . The alleles Glu-A1b, Glu-B1i, Glu-D1d, Glu-A3b, Glu-B3g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…These results indicate that allele Glu‐A3b had a more positive influence on rheological properties than allele Glu‐A3e . Generally, the negative effect of Glu‐A3e (null allele) on dough quality properties was reported in several previous studies . It is difficult to conclusively evaluate the contribution ranking of Glu‐3 alleles because most materials used in previous, numerous studies have different genetic backgrounds.…”
Section: Resultssupporting
confidence: 84%
“…These results indicate that allele Glu‐A3b had a more positive influence on rheological properties than allele Glu‐A3e . Generally, the negative effect of Glu‐A3e (null allele) on dough quality properties was reported in several previous studies . It is difficult to conclusively evaluate the contribution ranking of Glu‐3 alleles because most materials used in previous, numerous studies have different genetic backgrounds.…”
Section: Resultssupporting
confidence: 84%
“…The HMW-GS 5+10 combination encoded by complex Glu-D1 locus are associated with good baking quality and is therefore preferred over 2 +10 subunit combination, which is associated with poor baking quality (see Nucia et al 2019). However, the HMW-GS 5+10 are not common among Indian bread wheat cultivars (Ram 2003, Ram et al 2015, Patil et al 2015. Therefore, there is a need for the introgression and pyramiding of HMW-GS 5+10 along with high GPC into elite Indian bread wheat cultivars to improve the technological properties of the our.…”
Section: Introductionmentioning
confidence: 99%
“… Payne et al (1980 , 1987) established a standard of Glu-1 quality score based on SV that was widely used to evaluate the quality of wheat varieties ( Weegels et al, 1996 ; Gianibelli et al, 2001 ; Esmaeilzadeh Moghaddam et al, 2011 ). Ram et al (2015) found that Glu-B1i and Glu-D1d showed a highly significant positive effect ( P < 0.001) on SV and also had additive effects. The allelic genes of Glu-1 caused the SV variations of several or more than 10 units (ml) ( Wang et al, 2018 ; Chen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 89%